THE BENEFITS OF USING EDUCATIONAL TECHNOLOGIES IN THE ENGLISH LANGUAGE CLASSROOM - Tadjibaeva , Albina (Educational Research in Universal Sciences, 2023)
This article overviews the benefit sides of using educational technologies while teaching listening, speaking and writing to students of English as a second language as well as benefits and challenges of using it on both students and teachers.